2013
DOI: 10.1089/dia.2013.0081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence for the Earlier Initiation of Insulin Therapy in Type 2 Diabetes

Abstract: The natural history of type 2 diabetes mellitus (T2DM) is a relentless progression of b-cell failure and dysregulation of b-cell function with increasing metabolic derangement. Insulin remains the only glucose-lowering therapy that is efficacious throughout this continuum. However, the timing of introduction and the choice of insulin therapy remain contentious because of the heterogeneity of T2DM and the well-recognized behavioral and therapeutic challenges associated with this mode of therapy. Nevertheless, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 64 publications
2
71
0
9
Order By: Relevance
“…Together, these variables seem to point to an advantage in beginning insulin earlier. Some studies have addressed this point directly, and while the advantages of very early use of insulin over oral agents can be disputed, these studies do not suggest much in the way of detriment either [20,21]. Using the CORE Diabetes Model, Goodall et al [22] using data specific to the UK, suggested that starting insulin rather than continuing oral agents for a further 8 years would increase lifespan by 7.5 months on average, as well as improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these variables seem to point to an advantage in beginning insulin earlier. Some studies have addressed this point directly, and while the advantages of very early use of insulin over oral agents can be disputed, these studies do not suggest much in the way of detriment either [20,21]. Using the CORE Diabetes Model, Goodall et al [22] using data specific to the UK, suggested that starting insulin rather than continuing oral agents for a further 8 years would increase lifespan by 7.5 months on average, as well as improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…and low values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) [165]. The hydrophobic moiety of the surfactant also influences enhancement action.…”
Section: Hlb In Permeation Enhancementmentioning
confidence: 99%
“…improved absorption of heparin following jejunal delivery in rats in vivo [279]. These data are not surprising as the most effective non-ionic surfactants tested in oral peptide delivery have similar hydrocarbon (C 8 -12 ) and ethoxylate ( [8][9][10][11][12][13][14][15][16][17][18][19][20] ) chain length [280]. Not all ethoxylated lipoidal vehicles alter intestinal permeability, for example, Kolliphor® EL (BASF, Germany) [281] and Cremophor® RH60 [282] are poor PEs.…”
Section: Permeation Enhancement From Complex Lipoidal Dispersionsmentioning
confidence: 99%
“…35 Nevertheless, rather than occurring early in treatment progression, initiation and intensification of insulin regimens in practice is often delayed in the face of poor or worsening glycaemic control.…”
Section: Insulin Is Underusedmentioning
confidence: 99%